LiMnTiO4 with the Na0.44MnO2 Structure as a Positive Electrode for Lithium-Ion Batteries. Issue 3 (1st January 2016) - Amigues, A. M.; Glass, H. F. J.; Dutton, S. E.
Abstract : A metastable polymorph of LiMnTiO4 with the Na0.44 MnO2 structure has been synthesized via ion-exchange from its sodium analogue, NaMnTiO4 . The structure was determined from a combination of X-ray and Neutron Powder Diffraction data. LiMnTiO4 has the P bam space group, with a = 9.074(5), b = 24.97(1) and c = 2.899(2) Å. The shapes and dimensions of the channels are slightly modified as compared to NaMnTiO4 with displaced alkali metal positions and occupancies. LiMnTiO4 was cycled vs Li at room temperature and up to 0.89 lithium ions can be reversibly inserted into the structure, with a discharge capacity of 137 mAh/g after 20 cycles at C/20. At 60°C all the lithium is removed at the end of the first charge at C/20, with subsequent cycles showing reversible insertion of 1.06 Li-ions.